(IN)ADEQUATE CRIMINAL PROTECTION OF THE CAPITAL MARKET IN THE REPUBLIC OF SERBIA (EU and comparative law issues and challenges series (ECLIC), 2020)
Regulation 596/2014/EU and Directive 2014/57/EU were adopted in order to provide adequate protection of investors and the smooth functioning of the capital market in European Union (EU). They envisage the obligations of Member States to prescribe, under national law, misdemeanor and criminal sanctions for conduct that constitutes abuses in the capital market. Their aim was to provide the same level of criminal justice protection at the level of all EU countries. As EU candidate country, the Republic of Serbia has prescribed sanctions by the Law on the Capital Market, the Law on Takeovers of Joint Stock Companies and the Law on Open-Ended Investment Funds subject to Public Offering. Although serious abuses in the capital market of the Republic of Serbia constitute criminal offenses, in practice it seems impossible for prosecutors and courts to prove their existence. Therefore, we cannot say that there is adequate protection of investors or unhindered functioning of the capital market. Given that national courts do not recognize as valid circumstantial evidence, it is impossible to prove some of these acts without the use of specific evidentiary actions such as, for example, eavesdropping on telecommunications. However, the Criminal Procedure Code of the Republic of Serbia only provides for a limited number of criminal offenses to which such evidentiary actions can be applied. This provision does not cover offenses under the secondary criminal legislation and, therefore, offenses representing abuses in the capital market. In the previous period, the Securities Commission has filed several criminal charges against the perpetrators of such criminal offenses, however, the Public Prosecutor’s Office has not filed any lawsuit or notified the authorized applicant on the outcome of the proceedings. Such actions could further discourage institutions authorized to monitor legitimate capital market operations from filing criminal charges against capital market abusers in the future, some of which may be related to corporate business corruption. This could certainly have a negative impact on the decisions of both existing and potential investors in the capital market. This paper starts with the analysis of compliance of the regulations of the Republic of Serbia with Regulation 596/2014/EU and Directive 2014/57/EU, then points to the lack of provisions of the Criminal Procedure Code which provides for the limited application of special evidence in criminal proceedings. Based on this analysis the authors strive to make recommendations in order to improve the implementation of provisions that enable the suppression of criminal offenses which threaten the capital market integrity. In this way, we would like to point out that alignment with the acquis communautaire also implies the possibility of applying its standards in the territory of both candidate and EU Member States. Therefore, in order to achieve this goal, it is necessary not only to adopt new regulations, but also to harmonize the existing provisions of some other regulations which enable their implementation in the practice.